Patients With Femoroacetabular Impingement Obtain Information From Low-Quality Sources Online and Are Most Interested in Conservative Treatment and Expected Recovery - Johnathon R. McCormick, M.D; Benjamin Kerzner, B.S; Trevor A. Tuthill, B.S; Zeeshan A. Khan, B.A; Alexander J. Hodakowski, B.A., Sc.M; Dhanur Damodar, M.D; Luc M. Fortier, M.D; Suhas P. Dasari, M.D; Shane J. Nho, M.D., M.S; Jorge Chahla, M.D., Ph.D (Elsevier, 2023)
Purpose: To investigate the type of questions patients undergoing hip arthroscopy for femoroacetabular impingement (FAI) are searching online and determine the type and quality of the online sources from the top results to each query by the "people also ask" Google algorithm. Methods: Three search strings pertaining to FAI were carried out through Google. The webpage information was manually collected from the "People also ask" Google algorithm. Questions were categorized using Rothwell's classification method. Each website was assessed using Journal of the American Medical Association Benchmark Criteria for source quality. Results: A total of 286 unique questions were collected with their associated webpages. The most common questions included: "How do you treat femoroacetabular impingement and labral tears without surgery?" "What is the recovery process after hip arthroscopy and are there limitations after surgery?" and "How do you diagnose hip impingement and differentiate from other causes of hip pain?" The Rothwell Classification of questions were fact (43.4%), policy (34.3%), and value (20.6%). The most common webpage categories were Medical Practice (30.4%), Academic (25.8%), and Commercial (20.6%). The most common subcategories were Indications/Management (29.7%) and Pain (13.6%). Government websites had the highest average Journal of the American Medical Association score (3.42), whereas Single Surgeon Practice websites had the lowest (1.35). Conclusions: Commonly asked questions on Google regarding FAI and labral tears pertain to the indications and management of pathology as well as pain control and restrictions in activity. The majority of information is provided by medical practice, academic, and commercial sources, which have highly variable academic transparency. Clinical Relevance: By better understanding which questions patients ask online, surgeons can personalize patient education and enhance patient satisfaction and treatment outcomes after hip arthroscopy.